Formación en Herramientas de Mentoring en la Gerencia de ETIAN (2019)
The business world today is governed by constant changes, and these are the ones that modern managers face. Recognize that there are management tools that help keep employees motivated and within institutions is a challenge that no institution currently escapes. Mentoring as a management tool helps to give importance to the experts' knowledge and its value for employees, generating a relationship of trust between them, which translates into business productivity. The present article was a case study of qualitative approach, with non-experimental transsectional design, of descriptive scope; (Hernández Sampieri and another, 2007). The main discoveries of this work are translated into the implementation of Mentoring tools through the CERCA Model of Valderrama (2009).